A theoretical study on the photophysical properties of three iridium(III) complexes bearing tridentate chromophoric chelate by using the density functional theory and time-dependent density functional theory. Issue 1 (9th June 2021) - Han, Deming; Ge, Shumin; Ji, Wei
Abstract: The electronic structure and photophysical properties of three iridium(III) complexes bearing tridentate chromophoric chelate have been theoretically studied by using the DFT/TDDFT. The lowest lying singlet→singlet absorptions of all studied complexes are respectively located at 363 nm, 394 nm and 353 nm. The calculated emission wavelengths for all studied complexes are 503 nm, 486 nm and 493 nm, respectively. The calculated results show that the electron-accepting and electron-donating substituent groups have the important effect on the electronic structure and photophysical properties of all studied iridium complexes with tridentate ligands.